(untitled) (Journal of Computational Mathematics, 1994)
In this paper, the problem of finding the intersection of a triangular Bézier patch and a plane is studied. For the degree that one frequently encounters in practice, i.e. n=2,3, an efficient and reliable algorithm is obtained, and computational steps are presented.